Hydroxy-functionalized hyper-cross-linked ultra-microporous organic polymers for selective CO2 capture at room temperature - Samanta, Partha; Chandra, Priyanshu; Ghosh, Sujit K. (Beilstein Journal of Organic Chemistry, 2016)
Two hydroxy-functionalized hyper-cross-linked ultra-microporous compounds have been synthesized by Friedel–Crafts alkylation reaction and characterised with different spectroscopic techniques. Both compounds exhibit an efficient carbon dioxide uptake over other gases like N2, H2 and O2 at room temperature. A high isosteric heat of adsorption (Qst) has been obtained for both materials because of strong interactions between polar –OH groups and CO2 molecules.
Keywords: carbon dioxide capture; hyper-cross-linked polymer; metal-organic framework; microporous organic polymer